2017
DOI: 10.3847/1538-4357/836/1/121
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Short Period Quasi-periodic Pulsation in Solar X-Ray, Microwave, and EUV Emissions

Abstract: This paper presents the multi-wavelength analysis of a 13 s quasi-periodic pulsation (QPP) observed in hard X-ray (12-300 keV) and microwave (4.9-34 GHz) emissions during a C-class flare occurred on 21 September 2015. AIA 304 and 171Å images show an emerging loop/flux tube (L1) moving radially outward, which interacts with preexisting structures within the active region. The QPP was observed during the expansion and rising motion of L1. The Nobeyama Radioheliograph (NoRH) microwave images in 17/34 GHz channels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The list of observations presented does not claim to be complete, but it demonstrates that there are a lot of such observations and they are published quite regularly. 25 − 180 MHz range) corresponding to the hard X-ray and microwave emission peaks were detected, which demonstrated the period of about 40 − 50 s and were delayed after the microwave peaks by ≈ 10 s. Kumar et al (2017) detected non-harmonic QPPs with a shorter period of about 13 s in a C4.2 flare on 2015 September 21; the pulsations occurred simultaneously in hard X-rays (12 − 300 keV) and microwaves (4.9 − 34 GHz). Three type III bursts (in the 25 − 180 MHz range) were also detected, which likely corresponded to the hard X-ray and microwave emission peaks (had a similar repetition period), but were delayed with respect to the microwave peaks by ≈ 30 s. observed an event with even longer delay between the QPPs in hard X-rays and type III bursts: in an X1.6 flare on 2014 September 10, hard X-ray light curves (27−296 keV) contained three prominent peaks with a period of about 4 min; a similar period (but with up to 10 peaks) was detected in EUV emission.…”
Section: Of Course Oscillatorymentioning
confidence: 88%
“…The list of observations presented does not claim to be complete, but it demonstrates that there are a lot of such observations and they are published quite regularly. 25 − 180 MHz range) corresponding to the hard X-ray and microwave emission peaks were detected, which demonstrated the period of about 40 − 50 s and were delayed after the microwave peaks by ≈ 10 s. Kumar et al (2017) detected non-harmonic QPPs with a shorter period of about 13 s in a C4.2 flare on 2015 September 21; the pulsations occurred simultaneously in hard X-rays (12 − 300 keV) and microwaves (4.9 − 34 GHz). Three type III bursts (in the 25 − 180 MHz range) were also detected, which likely corresponded to the hard X-ray and microwave emission peaks (had a similar repetition period), but were delayed with respect to the microwave peaks by ≈ 30 s. observed an event with even longer delay between the QPPs in hard X-rays and type III bursts: in an X1.6 flare on 2014 September 10, hard X-ray light curves (27−296 keV) contained three prominent peaks with a period of about 4 min; a similar period (but with up to 10 peaks) was detected in EUV emission.…”
Section: Of Course Oscillatorymentioning
confidence: 88%
“…Such a short-time variability is a common feature detected in all phases of a flare, at all wavelengths, from radio to gamma-rays (e.g. Dolla et al 2012;Huang et al 2014;Inglis et al 2016;Kumar et al 2017;Pugh et al 2017b). The short-time variations occur in different parameters of the emission: its intensity, polarization, spectrum, spatial characteristics, etc.…”
Section: Introductionmentioning
confidence: 98%
“…They are observed both in cool and hot plasma ejections from the photosphere to the outer corona in the solar atmosphere. Until to-date, many kinds of jet activities have been observed in different spectral lines, such as Hα surges (Roy 1973;Liu & Kurokawa 2004;Jiang et al 2007), extreme ultraviolet (EUV) (Shen et al 2012;Li et al 2015;Liu et al 2015;Shen et al 2011;Nisticò et al 2015;Kumar et al 2017;Zhu et al 2017;Tian et al 2017Tian et al , 2018 and X-ray jets (Shibata et al 1992;Vasheghani Farahani et al 2009;Moore et al 2010Moore et al , 2013Pucci et al 2013;Sterling et al 2015;Moore et al 2018). Many researches indicated that most solar jets result from magnetic reconnection in the low solar atmosphere (Shibata et al 1992(Shibata et al , 1994Canfield et al 1996;Shimojo et al 1996Shimojo et al , 1998Liu & Zhang 2002;Jiang et al 2007;Shen et al 2011;Hong et al 2011;Shen et al 2014;Li et al 2015;Liu et al 2015;Sterling et al 2015;Li et al 2015;Xu et al 2016;Hong et al 2017;Shen et al 2017Shen et al , 2012Adams et al 2014;Schmieder et al 2015;…”
Section: Introductionmentioning
confidence: 99%